2021
DOI: 10.3389/fimmu.2021.674484
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Potential Yeast-Based Vaccine Platform for Theileria parva Infection in Cattle

Abstract: East Coast Fever (ECF), caused by the tick-borne apicomplexan parasite Theileria parva, remains one of the most important livestock diseases in sub-Saharan Africa with more than 1 million cattle dying from infection every year. Disease prevention relies on the so-called “Infection and Treatment Method” (ITM), which is costly, complex, laborious, difficult to standardise on a commercial scale and results in a parasite strain-specific, MHC class I-restricted cytotoxic T cell response. We therefore attempted to d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…S. cerevisiae has been one of the most popular heterologous expression hosts in biotechnology, and it is increasingly employed in oral vaccine development [ 10 16 , 37 41 ]. Our previous study [ 13 ] showed that the expression of LTB fused with a synthetic Dengue tetravalent antigen using S. cerevisiae was potentially useful as an oral vaccine against Dengue viruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. cerevisiae has been one of the most popular heterologous expression hosts in biotechnology, and it is increasingly employed in oral vaccine development [ 10 16 , 37 41 ]. Our previous study [ 13 ] showed that the expression of LTB fused with a synthetic Dengue tetravalent antigen using S. cerevisiae was potentially useful as an oral vaccine against Dengue viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its high-quality protein content and high vitamin levels distinguish S. cerevisiae as a favorable single cell organism useful for live and oral administration of pharmaceutical and feed products [ 8 , 9 ]. Furthermore, the strong adjuvant properties of yeast derivatives render it an attractive heterologous expression system for vaccine production and development [ 10 17 ]. A well-balanced immune response to dengue was observed when a yeast expression system was used to produce dengue virus epitope proteins [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. parva is a tick-borne hemoprotozoan that infects and transforms bovine lymphocytes (26, 27). Cow 224 had been immunised with a preparation of live T. parva sporozoites (“Infection and Treatment Method”) (28), which triggers an antigen-specific, MHC class I-restricted, cytotoxic T cell response among other immune reactions (29, 30). However, T. parva infection of cow 224 had been cleared via antiprotozoal drug treatment prior to blood sample collection and PBMC isolation for this work.…”
Section: Discussionmentioning
confidence: 99%
“…Method") (28), which triggers an antigen-specific, MHC class I-restricted, cytotoxic T cell response among other immune reactions (29,30). However, T. parva infection of cow 224 had been cleared via antiprotozoal drug treatment prior to blood sample collection and PBMC isolation for this work.…”
Section: Expression and Regulation Of Bominclementioning
confidence: 99%